Development of nursing handoff competency scale: a methodological study - Jiyoung Do; Sujin Shin (BMC, 2024)
Abstract Background Nursing handoff competency is the ability of the nurse performing the handoff to select and interpret the necessary information for patient care and to convey it efficiently to the nurse accepting the handoff. Nursing handoff is an important nursing task that ensures nursing care continuity, quality and patient safety. This study aimed to develop a scale to measure nursing handoff competency and verify its validity and reliability. Methods This study adopted a methodological design. A research process included three phases: (1) scale development (literature review and interviews); (2) scale validation (validity and reliability); (3) standard setting. Data were collected from 496 clinical nurses currently working in hospital wards, intensive care units, and emergency rooms, and who independently perform a handoff in South Korea. Results The final scale comprises a self-reported 4-points Ilert scale with 25 items based on four factors: knowledge on handoff methods, identification of patient information, judgment and transfer of nursing situation, and "formation of supportive relationships. Construct validity, criterion-related validity, and discrimination validities were verified and the fitness of the scale revealed good results in confirmatory factor analysis. The Cronbach's α of the whole tool was.912 and the cut-off score for satisfied/unsatisfied was.72. Conclusions The developed scale can evaluate the nurse's handoff competencies and determine whether training is necessary. The measurement results of the scale can be used to select training subjects and compose the contents of the education program.